The challenges of strategic management of the wastage produced due to earthquake in Kermanshah and Varzaghan-Ahar: A qualitative study - Sadegh Kazemi; Mehdi Mokhtari; Aliakbar Vaezi; Ibrahim Salmani; Mohammad Hassan Ehrampoush; Abbas Ali Dehghani Tafti; Hossein Fallahzadeh; Mojtaba Fattahi Ardakani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Strategic management of the wastage produced due to earthquakes has faced many challenges over the recent decade. Thus, the present study seeks to identify and explain the challenges in earthquake wastage strategic management. MATERIALS AND METHODS: The present qualitative study has been steered through a content analysis approach and conducted using semi-structured interviews and a purposive selection of 17 professors, experts, and managers experienced in the field of waste management in Kermanshah and Varzaghan-Ahar earthquakes over 2020-2021. Besides, the interviews were initially categorized using MAXQDA18 software. RESULTS: Analysis of the experiences and perception regarding the changes in strategic management of wastage produced due to Kermanshah and Varzaghan-Ahar earthquakes revealed 418 codes, 97 subcategories, 33 categories, and 8 main categories including management and leadership, organizational culture, planning, organizational learning, employee management, rules and regulations, resource management, and procedure management. CONCLUSION: Strategic waste management has not been implemented in a coherent, integrated, and well-planned manner in the cases of the Kermanshah and Varzaghan-Ahar earthquakes. The challenges of strategic waste management turned out to be due to various reasons which will result in many issues in achieving the goals and selecting the suitable method for resource and procedure management should they not be managed well. Hence, policymakers, managers, and executors in the field of crisis management and waste management in disasters -specifically earthquakes- must take the necessary measures to remove these barriers.